The Evaluation of Logistics-Oriented Economic Development Level Based on Principal Component Analysis and Cluster Analysis: The Case of Guangdong Province - Pan, Xia Pan; Jarrett, Jeffrey E (Asian Journal of Empirical Research, 2015)
This paper tries to cluster the cities in Guangdong Province, China according to their economic development levels. We intentionally separate a group of indicators for logistics and transportation development levels, therefore, the clustering results can be viewed as in accordance with logistics-oriented economic development levels. Before the clustering, we use principal component analysis to reduce the number of dimensions. The results of the final categories are consistent with what many people perceived about the clusters according to the city’s economic development levels, as well as how much the cities’ logistics is developed. This findings provide the business and public administration decision makers the references in their decisions on developing the respective city’s logistics and transportation.